Taguchi L25 (54) approach for methylene blue removal by polyethylene terephthalate nanofiber‐multi‐walled carbon nanotube composite - Essa, Wafa K.; Yasin, Suhad A.; Abdullah, Anwar H.; Thalji, Mohammad R.; Saeed, Ibtisam A.; Assiri, Mohammed A.; Chong, Kwok Feng; Ali, Gomaa A. M. (MDPI, 2022)
A membrane composed of polyethylene terephthalate nanofiber and multi‐walled carbon nanotubes (PET NF‐MWCNTs) composite is used to adsorb methylene blue (MB) dye from an aqueous solution. Scanning electron microscopy, Fourier transform infrared spectroscopy, and X‐ ray diffraction techniques are employed to study the surface properties of the adsorbent. Several parameters affecting dye adsorption (pH, MB dye initial concentration, PET NF‐MWCNTs dose, and contact time) are optimized for optimal removal efficiency (R, %) by using the Taguchi L25 (54) Orthogonal Array approach. According to the ANOVA results, pH has the highest contributing percentage at 71.01%, suggesting it has the most significant impact on removal efficiency. The adsorbent dose is the second most affected (12.08%), followed by the MB dye initial concentration of 5.91%, and the least affected is the contact time (1.81%). In addition, experimental findings confirm that the Langmuir isotherm is well‐fitted, suggesting a monolayer capping of MB dye on the PET‐NF‐MWCNT surface with a maximum adsorption capacity of 7.047 mg g−1. Also, the kinetic results are well‐suited to the pseudo‐second‐order model. There is a good agreement between the calculated (qe) and experimental values for the pseudo‐second‐order kinetic model.